6g+2(-6+2g)=1-g

Simple and best practice solution for 6g+2(-6+2g)=1-g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6g+2(-6+2g)=1-g equation:


Simplifying
6g + 2(-6 + 2g) = 1 + -1g
6g + (-6 * 2 + 2g * 2) = 1 + -1g
6g + (-12 + 4g) = 1 + -1g

Reorder the terms:
-12 + 6g + 4g = 1 + -1g

Combine like terms: 6g + 4g = 10g
-12 + 10g = 1 + -1g

Solving
-12 + 10g = 1 + -1g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add 'g' to each side of the equation.
-12 + 10g + g = 1 + -1g + g

Combine like terms: 10g + g = 11g
-12 + 11g = 1 + -1g + g

Combine like terms: -1g + g = 0
-12 + 11g = 1 + 0
-12 + 11g = 1

Add '12' to each side of the equation.
-12 + 12 + 11g = 1 + 12

Combine like terms: -12 + 12 = 0
0 + 11g = 1 + 12
11g = 1 + 12

Combine like terms: 1 + 12 = 13
11g = 13

Divide each side by '11'.
g = 1.181818182

Simplifying
g = 1.181818182

See similar equations:

| 3x+a=56x | | x+2x-1=4x+3 | | 11x+20=2x+128 | | 3+3m-1=7m+20-2m | | 36=18x^2 | | 3x+6+7x+4=90 | | 11-8x=111-43x | | .5x=4x-21 | | -16x^2+x-1087=0 | | 2x^2+7x+8=0 | | x^2+y^2+10x+8y+4=0 | | (18*2)-1=a | | 2g+2(-6+3g)=1-g | | 9y+17y=104 | | 11+9y=119 | | x+10/10=18/12 | | -5x-3y=10 | | 5x+[(17-11x)-(16x-10)]=36-9x | | W+-41=0 | | -7y+6=41y-3 | | x+(-64)=-70 | | ln(2x+1)=ln(x+3) | | 10a-2(2a-7)=68 | | -10.0x=80.8 | | n/3+4.6=21.6 | | P=164l+240w | | -10x-171=12x+93 | | 8t+5t=6t+1 | | 2x(x-1)-4=(2x-3)(x+1)-2(3x+2) | | 2c-4=-2+8c | | -38-9x=46-6x | | 3m=18 |

Equations solver categories